Uso del poliacrilato de potasio en el cultivo de vid (Vitis vinifera) en la provincia de Santa Elena - Avilés Morán, Jackson David (2022)
This document synthesizes relevant information on the use of new technologies in the agricultural sector to solve a current problem such as the lack of rainfall in arid areas of Ecuador, taking the province of Santa Elena as the place of study. Potassium polyacrylate turns out to be a sustainable alternative for crops established in places with deficit irrigation because, being a hydrogel, it has the capacity to absorb water up to 400 times its own weight and then gradually releases it to be absorbed by the roots of plants. The reference crop subject to analysis in this research work is the vid crop (Vitis vinifera) since in recent years it is taking a great boom in the Santa Elena Peninsula and the use of hydrogel has managed to provide great contributions that optimize the harvest yields. The execution of this project was carried out using exploratory and explanatory research techniques. It was obtained as results that the experimental control treatments registered lower humidity values compared to the treatments where the hydrogel was used despite having subjected them all equally to extreme conditions. At the end of this document, it is concluded that the application of potassium polyacrylate in grapevine cultivation or in any other crop should not be considered as an irrigation system but rather as a water enhancer, always taking all the necessary precautions at the time of the dosage application and the way we incorporate the product in the soil.